Rekonstruksi Fiqh Jinayah terhadap Perda Syariat Islam - Sahid HM, Sahid HM (ISLAMICA: Jurnal Studi Keislaman, 2012)
This paper poses a question whether Syariâah can be adopted as a regional/provincial law in Indonesia or not? The question has many sides. First, the many provinces in Indonesia have different religious and cultural setting, making them varied in their reception not only to Syariâah but also to Islam itself. Even the province where Muslims are majority, Syariâah is not always ready to apply. Second, the formalization of Syariâah has provoked an uneasy response from many non-Muslims and also from many Muslims who are not happy with the formalization of Syariâah. Third, the provincial law has thus far been good in some provinces, giving no chance for the Syariâah law to interfere. It is these problems that this paper is concerned with. Some aspects of the Syariâah criminal law that many have attempted to be formalized will be discussed here such as the law of fornication, of drugs and beer, of prostitution, and of religious transgression.